Effect of dietary garlic (Allium sativum) on the zootechnical performance and health indicators of aquatic animals: A mini-review (2023)
Considerable efforts have been made by modern aquaculture to mitigate the environmental damages caused by its practices while also attempting to improve the quality of the aquatic organisms by promoting alternatives, such as the use of natural products, like garlic (Allium sativum), and instead of chemical agents. Garlic has multiple properties, including antifungal, antibacterial, antiviral, antitoxic, and anticancer effects. In fish, the antiparasitic activity of garlic is one of the most reported effects in the literature, mainly using immersion baths for aquatic organisms. Using garlic also has an antimicrobial effect on the culture of aquatic organisms. Therefore, this review focuses on the impact of garlic on the health and production of aquatic organisms.